Mutation spectrum in epilepsy and seizure disorders in a group of Emirati patients: a retrospective cohort study and literature review - Aisha AlShamsi; Sema Koruturk (Egyptian Journal of Medical Human Genetics)
Abstract Background Epilepsy is a major neurological disorder worldwide, with common risk factors identified including consanguinity, family history, and history of perinatal infections or insults. Despite a high rate of consanguineous marriage among the Emirati population, there is limited data on genetic epilepsy in this group. Aims This study aims to investigate the genetic landscape of epilepsy among the Emirati patients, with a focus on identifying potential founder mutations over a 10-year period. Methods A retrospective chart review was conducted for all Emirati patients with seizure disorders or epilepsy assessed by clinical geneticists at Tawam Hospital between January 2012 and December 2022. The genetic tests were performed based on the patient's clinical phenotypes and family history, and included chromosome microarray, targeted variant testing, next-generation sequencing, or whole-exome sequencing (solo or trio). At the same time, the authors conducted a literature review using PubMed to identify all previously reported articles related to seizure disorders and epilepsy genes in the United Arab Emirates (UAE). Results A total of 117 patients with seizure disorders were analyzed, consisting of 58% males and 42% females. The youngest patient was evaluated on the first day of life, and the oldest patient was 16 years old. Consanguinity and family history were documented in 62% of cases. A positive molecular diagnosis was identified in 68% of patients, with 52% having autosomal recessive disorders, 30% having autosomal dominant disorders, four patients having X-linked related disorders, and three patients having mitochondrial disorders. Seven patients were found to have chromosomal abnormalities. Thirteen novel variants were identified. Missense mutations represented the most prevalent variant type identified. The ADPRHL2 gene variant was the most commonly identified, followed by the repeat expansion in the CSTB gene. The phenotypes observed among the studied patients included isolated epilepsy, dysmorphic features, neurodevelopmental disorders, and concurrent inborn errors of metabolism. Conclusion The novel variants identified in this study represent an area for future research. Further studies are required to accurately estimate the prevalence and incidence of seizure disorders and epilepsy in the Emirati population to improve healthcare planning. Future research on targeted gene therapies may also help establish focused treatment options. The findings from this study are crucial for accurate diagnosis, effective disease management, the potential for personalized medicine, and informed genetic counseling.